SOCIO-ECONOMIC STATUS AND ACADEMIC PERFORMANCE OF PUPILS IN PUBLIC ELEMENTARY SCHOOLS IN SANTA ANA DISTRICT - SAGARIO, ARJAY; QUINTO, JINKY DYLAN; ANTONIO, RAVEN (International Journal of Arts, Sciences and Education, 2023)
This study investigated the effect of socioeconomic status on the academic performance of the Grade VI Pupils from the select central and non-central elementary schools in Santa Ana District. It utilized a descriptive-correlational research design and carried out a total population of 113 respondents from the selected public elementary schools. A checklist questionnaire was used to gather necessary data which include the Socioeconomic profile of the respondents and their grades for 1st and 2nd grading. Results revealed that family household size, parents’ educational attainment, and parents’ occupation have a significant effect on the academic performance of the learners. This study is believed to have an impact on broadening the ideas, knowledge, and understanding of the families, parents, and government agencies on how to improve the education of every Filipino child. Keywords: Economic Status, Academic Performance, Family Size, Parent’s Occupation, Educational attainment